Prevalence and severity of periodontal diseases among Nepalese adults - a hospital based study - Rajkarnikar, J; Acharya, J (Journal of College of Medical Sciences-Nepal, 2015)
Objective The present study was undertaken to determine the prevalence of periodontal diseases among adults visiting the dental department of a hospital based in Jorpati. Methods Four hundred and seventeen patients were randomly taken from a dental hospital situated in Jorpati during the time period of March 2013 to August 2013. All patients visiting the dental department who fulfilled the inclusion criteria were included in the study. The data included patients overall information along with their chief complaint, gingival bleeding on probing (BOP), probing depth (PD), frequency of brushing, adverse habits and the diagnosis of the patients examined. Results We found that 52.5% suffered from gingivitis and 47.5% suffered from periodontitis. Also 28.3% suffered from localized and 18% suffered from generalized form of periodontitis. There was no statistically significant difference in the gender when the prevalence of periodontal disease was compared. 51.4% of male and 44.4% of female was seen to be affected with periodontitis. Also habits like smoking and intake of smokeless tobacco was seen to be associated with periodontitis. Regarding the age group more number of patients in the age group of >50 years were seen to be suffering from periodontitis (84.3%) as compared to age group of <35 years (25.9%). Conclusion There is high prevalence of periodontitis and gingivitis in the studied population. Periodontitis was seen to be more prevalent as age advanced which can be attributed mainly to untreated gingivitis. However, no significant difference was seen in the prevalence of periodontitis with respect to gender. Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 11-16